Analisis Wacana Kritis Cerpen Dawir, Turah, dan Totol Karya Ahmad Tohari: Critical Discourse Analysis of the Short Stories Dawir, Turah, and Totol by Ahmad Tohari - Wahyu Lazuardi; Ida Nurul Chasanah; Bramantio Bramantio (Information Technology and Science(ITScience), 2026)
The research begins with the problem that critical discourse analysis in literary works often stops at the theme of gender inequality without dissecting the narrative mechanisms that produce it. This study aims to reveal patriarchy as a result of discursive work by integrating Fairclough and Sara Mills' discourse analysis in the short stories Dawir, Turah, and Totol by Ahamad Tohari. The method used is qualitative, with integrated critical discourse analysis, namely the dimension of discursive practice to read the social context, as well as the analysis of the positions of the narrative subjects and objects, and the reader's position to trace the mechanism of the narrative. Data in the form of narrative discourse units, dialogues, character descriptions, and narrative points of view were collected through reading and note-taking, then analyzed in stages. The results of the study show four main findings, namely the terminal functions as a social practice that normalizes power relations; Turah is consistently positioned as the object of the narrative while the authority of meaning rests with the narrator and male characters; the text constructs the reader's position to follow a masculine perspective; and patriarchy emerges as a result of the integration of the social context and the narrative structure. These findings emphasize that ideology operates through the structure of the text, not just its content. This study concludes that integrating Fairclough and Sara Mills effectively extends critical discourse analysis beyond linguistic aspects to narrative mechanisms and reader construction, and opens new ways of reading the representation of marginalized women in literature.